PENGEMBANGAN BATIK DEMAKAN SEBAGAI WUJUD KEARIFAN LOKAL UNTUK MENINGKATKAN KINERJA PEMASARAN MELALUI INOVASI PRODUK PADA UKM KERAJINAN BATIK KABUPATEN DEMAK - Solikhatun, Is; Musthofa, Asâ€™ad (JAB (Jurnal Akuntansi & Bisnis), 2019)
ABSTRACTÂ The purpose of this study was to determine the development of Demakan batik as a form of local wisdom to improve marketing performance through product innovation at UKM batik handicrafts. This type of research is explanatory. Research sample with the saturated sample method. Data collection techniques with questionnaires and interviews. The measurement scale uses a Likert scale and the data analysis uses linear regression with intervening variables. The results of the study are that there is a significant influence on entrepreneurial orientation, market orientation on product innovation and there is a significant influence on product innovation on marketing performance.Keywords : entrepreneurial orientation, market orientation, product innovation and marketing performance.